An Evaluation of Complications Following Ultrasound-Guided Regional Block Anesthesia in Outpatient Hand Surgery. (March 2021) - Voskeridjian, Armen C.; Calem, Daniel; Rivlin, Michael; Beredjiklian, Pedro K.; Wang, Mark L.
Background: Ultrasound-guided (USG) assistance has contributed to the acceptance of regional anesthesia as a safe and efficient alternative to traditional general anesthesia. However, limited data exist regarding the safety of supraclavicular blocks used in common hand surgery procedures. The purpose of this retrospective study was to evaluate a large sample of cases to determine the effectiveness and complication rate of supraclavicular nerve blocks and confirm the safety of its use within the ambulatory surgery center (ASC) setting.Methods: Nerve blocks for the upper extremity were performed via the supraclavicular approach using the USG technique. Records were analyzed for all patients monitored during the immediate postoperative recovery and step-down phases at the ASC and contacted by phone or evaluated within 2 weeks at their first postoperative visit. Adverse outcomes related to the regional block anesthesia were identified via phone interview or postoperative surgical visit and documented.Results: In all, 713 records were reviewed with 56% female (n = 398) and 44% male (n = 315) patients. Of the 713 cases, 4 adverse events were identified (0.6%, 95% confidence interval [%]), including 2 abnormal reactions to the nerve block and 2 incomplete blocks with inadequate pain control.Conclusions: This study is the first report to evaluate a large sample of outpatient hand procedures at a high-volume ASC. We can report no clinically significant pulmonary or neurovascular complications with the use of USG supraclavicular nerve block techniques, further supporting its establishment as a safe and efficient procedure, yielding a low complication rate.